Clinical Profile, Reporting Pathway and Management of Serious Adverse Events Following Administration of nOPV2 in Children Aged 0-5 Years in Benin - Setondji Padonou; Angela Sasse; Jennifer Olofindji; Landry Kaucley; Badirou Aguemon (World Journal of Public Health, 2026)
Background: Characterising the clinical profile, reporting pathway and management of adverse events following immunization (AEFIs) is essential for strengthening vaccine safety surveillance. This analysis focuses exclusively on severe non-fatal cases reported following administration of the novel oral polio vaccine type 2 (nOPV2) in Benin. Methods: A retrospective descriptive case series, embedded within a national case-control investigation, was conducted throughtout Benin from August to November 2025. This analysis included 510 serious non-fatal AEFI cases with usable clinical, reporting and management data; 49 fatal cases under seperate investigation were excluded. Results: The mean age was 25.2 months, and 52.5% of the children were boys. High fever (84.9%), diarrhoea (22.0%), and seizures (17.5%) were the most frequently reported manifestations, with a mean time to onset of 4.2 days. Management included rehydration or infusion (88.0%), antipyretics (87.0%), antibiotics (59.0%), blood transfusions (35.0%), and anticonvulsants (9.0%). The reporting outcome was documented for 494 of 510 cases (96.9%); among these, 493 received immediate care or referral (99.8%). Conclusion: The clinical profile was dominated by fever, diarrhoea, and seizures, with management was mainly symptomatic. The health system generaly responded rapidly after an alert, although the delay before caregiver reporting remained variable. No causal relationship between vaccination and reported events can be established from this descriptive analysis.